Identification of the novel HLA‐B allele, HLA‐B*52:56 by sequence‐based typing in a Chinese individual. (18th February 2019) - Li, Wangxia; Xu, Jing; Yang, Ru; Shi, Weidong
Abstract : HLA‐B*52:56 differs from HLA‐B*52:01:01:01 by one nucleotide exchange at position 107(T > C) with one amino exchange.